14 Diazoxide-induced antiarrhythmic protection in the non-diabetic and diabetic rat heart does not require activation of PI3-kinase/AKT. Issue 1 (10th December 2010) - Matejikova, J; Pancza, D; Kolar, F; Ravingerova, T
Abstract : Mitochondrial KATP channels (mitoKATP) activation interacting with phosphatidylinositol 3-kinase (PI3K)/Akt has been suggested as a key element in preconditioning protection against lethal myocardial ischaemia/reperfusion injury in healthy heart, 1 while its antiarrhythmic effects are less elucidated.2 Experimental studies of diabetes mellitus revealed, besides higher vulnerability to ischaemia, paradoxically enhanced ischaemic tolerance3 that has been proposed to share some molecular mechanisms with preconditioning in non-diabetic heart. We explored the involvement of PI3K/Akt in preconditioning-like effect of mitoKATP opener diazoxide on susceptibility to ischaemia-induced ventricular tachyarrhythmias in rats made diabetic with streptozotocin (65 mg/kg, 1 week) and in non-diabetic animals. Langendorff-perfused hearts of both groups were subjected to 30-min LAD occlusion with or without prior 15-min perfusion with diazoxide given either alone or combined with PI3K/Akt inhibitor wortmannin administered in concentration that abolished infarct size limitation and Akt activation. Total number of premature ventricular complexes, episodes of ventricular tachycardia and its duration were significantly reduced in the diabetic hearts (225±41, 5±2.9 and 15±11 s vs 551±61, 11.1±2 and 42±8 s in non-diabetic controls, respectively; p<0.05). Pre-treatment with diazoxide induced antiarrhythmic effects in both groups, while wortmannin alone did not modify arrhythmogenesis. Bracketing of diazoxide with wortmannin did not reverse antiarrhythmic protection in any of the groups. Conclusions: the results indicate that PI3K/Akt activity is not required for the suppression of ischaemia-induced arrhythmias conferred by mitoKATP opening in the normal and diabetic rat heart.